Innovations in defence support systems -2 socio-technical systems - Jain, Lakhmi C.; Aidman, Eugene V.; Abeynayake, Canicious; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book presents a sample of the state-of-art research on defence support systems. The focus of the volume is on the design and optimization of socio-technical systems and their performance in defence contexts. Conceptual and methodological considerations for the development of such systems and criteria likely to be useful in their evaluation are discussed, along with their conceptual underpinnings in total system per
Advances in Defence Support Systems -- Multi-Robot Task Allocation for Performing Cooperative Foraging Tasks in an Initially Unknown Environment -- Formal-Language-Oriented Foundation of Dynamics of Human Crowds Using Topos-Theory -- Methodology for the Evaluation of an International Airport Automated Border Control Processing System -- The role of the human operator in image- based airport security technologies -- Assessment of the ThruVision T4000 Passive Terahertz camera: A Human Factors Case Study -- Assessment of the ThruVision T4000 Passive Terahertz camera: A Human Factors Case Study -- Reliability Evaluation of Defence Support Systems.
Electronic reproduction.
Keywords: Electronic books; Military art and science -- Technological innovations; Electronics in military engineering; Military art and science -- Data processing; System design